Chaotic systems with pseudorandom number generate to protect the transmitted data of wireless network - Heyam A. Marzog; Marwa Jaleel Mohsin; Mohammed Azher Therib (Institute of Advanced Engineering and Science, 2021)
Communication techniques have witnessed rapid development in recent years, especially the internet and the mobile network, which led to rapid data transmission. The latest developments, in turn, have come out with advanced decisions to secure information from eavesdropping. Myriad in-depth studies in cryptography. It was implemented with the intention of proposing a revolutionary solution to protect data by encryption techniques, tend maps, and logistics. This work had proposed a new design to the generator of pseudo-random numbers (GPRN) which had utilized multi chaotic systems. Synchronization of Multi-parameters chaotic arises in many applications, in natural or industrial systems. Many methods have been introduced for using a chaotic system in the encryption of data. Analysis of security of chaotic system had been executed on key sensitivity and keyspace.